ANALISIS KEPATUHAN WAJIB PAJAK - Mrs Eliana (Sekolah Menengah Kejuruan (SMK) Pustek, 2018)
The purpose of this study is to determine the effect of motivation, fiscal services and tax sanctions through financial conditions on the compliance of individual taxpayers, both partial and simultaneous. The research method used in this research is quantitative with descriptive explanations. The analysis method used is path analysis with a sample size of 100 respondents and the sampling technique used is random sampling technique. Hypothesis test results prove work motivation has a significant effect on tax compliance by 0,139. The tax authorities have a significant effect on tax compliance by 0,178. Tax sanctions have a significant effect on tax compliance with a coefficient of 0,553. The results of simultaneous analysis prove that motivation, fiscal services, tax sanctions and financial conditions have a significant effect with a coefficient of determination of 95%, the rest is explained by other variables outside this study. While the results of the moderation analysis (through) proved to be motivational, tax authorities and tax sanctions through financial conditions significantly influence tax compliance